The biological function of Atractylodes lancea and its application in animal husbandry: a review - Gao, Yang; Wang, Dong; Ma, Xue; Li, Jiahui; Wang, Difei; Chen, Bo; Yang, Xuexi; Leng, Huan (Frontiers in Veterinary Science, 2025)
Atractylodes lancea, is a herbaceous plant of the Asteraceae family which is a traditional Chinese herbal medicine. It is often used for dehumidification, antiemetics, spleen strengthening and antipyretic effects. Atractylodes lancea is rich in various bio-active substances and has many biological functions, for instance anti-inflammatory, antioxidant and antiviral effects. Therefore, it is widely used in animal production, such as relieving heat stress, protecting intestinal health and regulating immunity. In recent years, it has received widespread attention in green cultivation. This article reviews the biological functions of Atractylodes lancea and looks forward to its application prospects in animal husbandry, in order to provide a theoretical basis for Atractylodes lancea to become a new feed additive in animal production.